Intranasal Lentiviral Vector-Mediated Antibody Delivery Confers Reduction of SARS-CoV-2 Infection in Elderly and Immunocompromised Mice - Du, Yue; Zhang, Shengnan; Zhang, Zhaoyong; Miah, Kamran M.; Wei, Peilan; Zhang, Lu; Zhu, Yuhui; Li, Zhengtu; Ye, Feng; Gill, Deborah R.; Hyde, Stephen C.; Wang, Yanqun; et al. (Frontiers in Immunology, 2022)
Vaccines for COVID-19 are now a crucial public health need, but the degree of protection provided by conventional vaccinations for individuals with compromised immune systems is unclear. The use of viral vectors to express neutralizing monoclonal antibodies (mAbs) in the lung is an alternative approach that does not wholly depend on individuals having intact immune systems and responses. Here we identified an anti-SARS-CoV-2 monoclonal antibody, NC0321, which can efficiently neutralize a range of SARS-CoV-2 variants, including Alpha, Beta, Delta and Eta. Both prophylactic and therapeutic NC0321 treatments effectively protected mice from SARS-CoV-2 infection. Notably, we adopted viral vector-mediated delivery of NC0321 IgG1 as an attractive approach to prevent SARS-CoV-2 infection. The NC0321 IgG1 expression in proximal airway, expressed by a single direct in vivo intranasal (I.N.) administration of a self-inactivating and recombinant lentiviral vector (rSIV.F/HN-NC0321), can protect young, elderly and immunocompromised mice against mouse-adapted SARS-CoV-2 surrogate challenge. Long-term monitoring indicated that rSIV.F/HN-NC0321 mediated the IgG expression well along the airway of young and SCID mice, and no statistical difference in the NC0321 expression level in the lungs of young and SCID mice was observed. A single I.N. dose of rSIV.F/HN-NC0321 30 or 180 days prior to SARS-CoV-2 challenge significantly reduced lung SARS-CoV-2 titres in an Ad5-hACE2 transduced mouse model, reconfirming that this vectored immunoprophylaxis strategy could be useful, especially for those individuals who cannot gain effective immunity from existing vaccines and could potentially prevent clinical sequelae.